AN EMPIRICAL INVESTIGATION INTO THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON STOCK PRICE PERFORMANCE IN THE INDIAN BANKING SECTOR: A CASE STUDY OF HDFC BANK - Oraon, Atul (Indian Journal of Finance and Banking, 2025)
This research examines the correlation between HDFC Bank’s Corporate Social Responsibility (CSR) initiatives and the stock price reaction. The project utilises secondary data from CSR reports and stock price movements, employing quantitative methods such as correlation analysis and event study methodology to determine whether CSR activities affect investor perceptions and, in turn, market performance. The study aims to examine whether HDFC Bank’s Corporate Social Responsibility (CSR) initiatives influence its stock market performance by analysing the relationships among CSR expenditure, overall stock prices, and short-term stock returns as indicators of market sentiment. The study employed a quantitative research design, utilising secondary data collected from HDFC Bank’s CSR reports and historical stock price records. Two methods were used: first, a Correlation analysis, and second, an event study to evaluate the association between CSR spending, average stock prices, and 3-month short-term returns. The results indicate a strong positive relationship between CSR expenditure and average stock price levels (r = 0.805, p = 0.016), suggesting that higher CSR spending may enhance investor confidence and long-term valuation. However, CSR expenditure showed a weak, non-significant relationship with short-term stock returns (r = –0.331, p = 0.424), as supported by the regression results, which had low explanatory power (R² = 10.9%). That confirms that CSR contributes more to long-term reputation and sustainable value creation than to short-term price movements. This study contributes to the limited Indian evidence on how CSR spending affects financial markets by focusing specifically on HDFC Bank—a central private-sector bank with consistent CSR engagement. Rather than examining broad market trends, this research provides a bank-specific, event-focused analysis that distinguishes between long-term valuation effects and short-term return behaviour. The results highlight CSR as a meaningful non-financial indicator of corporate sustainability and investor perception in the Indian context. JEL Classification Codes: G11, G12, G14, G17, G21, G38.